Wave Breaker Types on a Smooth and Impermeable 1:10 Slope - María Victoria Moragues; María Clavero; Miguel Á. Losada (Journal of Marine Science and Engineering, 2020)
This research identified the types of wave breaker on a non-overtoppable, smooth and impermeable 1:10 slope under regular waves. Experimental tests were carried out in the Atmosphere-Ocean Interaction Flume of the Andalusian Institute for Earth System Research (University of Granada). Using the experimental space [log(h/L)–log(H/L)] and the alternate slope similarity parameter [χ = log (h/L H/L)], a complete set of breaker types was identified. Four types of wave breaker were then added to Galvin’s classification. Our results showed that the value of the Iribarren number was not sufficient to predict the expected type of wave breaker on the slope. Except for spilling and early plunging breakers, no biunivocal relationship was found between Ir and the type of breaker. The data obtained in the physical model were further enriched with the results of the flow characteristics and the wave energy transformation coefficients obtained with the IH-2VOF numerical model on a 1:10 impermeable slope. This research study, presented in this paper, showed that the Iribarren number is not a convenient wave breaking similarity parameter.